Resilience, Social Support, and Quality of Life Among People Living with HIV/AIDS - Firman Firman; Sri Yona; Agung Waluyo (Jurnal Keperawatan Indonesia, 2025)
One of the most common challenges faced by people living with human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) is a low quality of life, particularly during the coronavirus disease 2019 (COVID-19) pandemic, as they are considered a vulnerable group. This study aimed to examine the relationship between resilience, social support, and quality of life among people living with HIV/AIDS during the pandemic. Conducted as a cross-sectional study, it involved 433 respondents. Data collection was carried out using a questionnaire, with Connor–Davidson Resilience Scale-25 (CD-RISC-25), Multidimensional Scale of Perceived Social Support (MSPSS), and World Health Organization Quality of Life–HIV Brief Version (WHO QoL-HIV-BREF) as the study instruments. The results indicated that resilience and social support were significantly associated with quality of life (p = 0.000; p = 0.000). Multiple logistic regression analysis identified resilience as the dominant factor influencing quality of life in people living with HIV (OR = 59.533). Respondents with high resilience were found to have a 59.53 times greater likelihood of experiencing a good quality of life compared to those with medium and low resilience after adjusting for marital status, income status, and length of time since HIV diagnosis. Resilience plays a crucial role in determining a person’s quality of life. HIV patients who actively participated in foundation-based assistance demonstrated greater optimism and a more positive acceptance of their condition, enabling them to cope with difficulties better. Keywords: HIV/AIDS, resilience, social support, quality of life   Abstrak Resiliensi, Dukungan Sosial, dan Kualitas Hidup Penderita HIV/AIDS. Salah satu tantangan yang paling umum dihadapi oleh penderita HIV/AIDS adalah rendahnya kualitas hidup, terutama saat pandemi COVID-19, karena mereka termasuk dalam kelompok rentan. Penelitian ini bertujuan untuk menguji hubungan antara resiliensi, dukungan sosial, dan kualitas hidup pada orang dengan HIV/AIDS di masa pandemi. Penelitian ini merupakan penelitian cross-sectional yang melibatkan 433 responden. Pengumpulan data dilakukan dengan menggunakan kuesioner Connor–Davidson Resilience Scale-25 (CD-RISC-25), Multidimensional Scale of Perceived Social Support (MSPSS), dan World Health Organization Quality of Life–HIV Brief Version (WHO QoL-HIV-BREF) sebagai instrumen penelitian. Hasil penelitian menunujukkan bahwa resiliensi dan dukungan sosial memiliki hubungan yang signifikan dengan kualitas hidup (p = 0,000; p = 0,000). Analisis regresi logistik berganda menunjukkan bahwa resiliensi merupakan faktor dominan yang memengaruhi kualitas hidup orang dengan HIV (OR = 59,533). Responden dengan resiliensi tinggi memiliki kemungkinan 59,53 kali lebih besar untuk memiliki kualitas hidup yang baik dibandingkan dengan responden dengan resiliensi sedang dan rendah, setelah mempertimbangkan status perkawinan, pendapatan, dan durasi sejak didiagnosa HIV. Resiliensi berperan penting terhadap kualitas hidup seseorang. Pasien HIV yang terlibat aktif dalam mengikuti pendampingan berbasis lembaga menunjukan sikap yang lebih optimis dan penerimaan yang lebih positif terhadap kondisi mereka, sehingga membuat mereka mampu menghadapi tantangan dengan lebih baik. Kata Kunci: dukungan sosial, HIV/AIDS, kualitas hidup, resiliensi